Familial desminopathy: myopathy with accumulation of desmin-type intermediate filaments. Issue 6 (June 1993) - Vajsar, J; Becker, L E; Freedom, R M; Murphy, E G
Abstract : Two siblings developed cardiomyopathy several years before slowly progressive muscle weakness. Skeletal muscle biopsy specimens showed subsarcolemmal crescents of dark eosinophilic material in both type I and type II fibres. Immunohistochemically the subsarcolemmal material stained positively for the intermediate filament protein desmin and for the heat shock protein ubiquitin but for no other cytoskeletal proteins. Ultrastructurally the subsarcolemmal deposits consisted of aggregates of granular and filamentous material arising from Z-bands. Follow up muscle biopsies six years later showed an increased number of the muscle fibres that contained subsarcolemmal aggregates that stained positively for desmin and ubiquitin. These clinical and pathological features characterise a rare familial myopathy associated with an unusual distribution of desmin intermediate filament proteins in skeletal and probably also cardiac muscle.